PRAKTEK PEMILIHAN JODOH OLEH ORANG TUA PADA ANAK GADISNYA DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Idris, Muhammad; PancasilawatI, Abnan; Andaryuni, Lilik (Ekonomi Syariah STAI Sangatta Kutai Timur, 2022)
The practice of matchmaking for children by parents in Indonesia is still common. This has the potential to violate laws and regulations, both positive law and Islamic law in Indonesia. Because usually in matchmaking, children tend not to be given the right to make choices in finding a life partner. So that the child is forced to undergo his marriage. As a result, the ultimate goal of a marriage to form a sakinah, mawaddah, and warahmah family will not be achieved.This paper was appointed by the author to find out how the practice of choosing a mate by parents for their daughters in North Sangatta District in the perspective of positive law and Islamic law. This research uses qualitative research with the research approach used is sociological juridical where this research is carried out to obtain legal knowledge empirically by going directly to the field. Data collection techniques in the form of observation, interviews, and documentation. The technique of taking respondents by means of snowball is a method of taking samples in a chain and random way.The results of this study indicate that the practice of matchmaking for children in North Sangatta District is in accordance with the provisions of positive law and Islamic law in Indonesia.Keywords: Selection of matchmaking, girls, positive legal perspective and Islamic law.